(untitled) (Nigerian Journal of Physiological Sciences, 2023)
The Coronavirus-19 transmitted through physical contact, droplets, and fomites caused severe respiratory disease resulting in high mortality worldwide. The COVID-19 pandemic caused innumerable hardships, panic, and restrictions of movement which negatively affected the assessment of healthcare services like breast cancer diagnosis in many countries. The results from the histopathological diagnosis of breast tumours have been routinely employed for the treatment and management of these diseases. This study investigated the impact of the COVID-19 pandemic on the histopathological diagnosis of breast tumours in Calabar. A retrospective study of the newly diagnosed breast tumours recorded in the Histopathology Laboratory register during the COVID-19 and the post-COVID-19 recovery from January 2020-February 2021 was compared with cases diagnosed before the pandemic from January 2018 to February 2019. Descriptive and inferential statistics and the Artificial Neural Network (ANN) of Statistical Package for Social Sciences (SPSS) were used for data analysis. New breast tumours diagnosed based on month showed low rates of 2.4% and 1.2% during the first and second waves of the pandemic respectively. The diagnosed cases increased to 11.8% and 8.2% after the first and second waves of the virus respectively. There was a significantly strong negative correlation between the COVID-19 pandemic and lockdown measures with breast tumour diagnosis (r=-0.919, p=0.001). More benign tumours of 56(58.3%) cases with a mean age of 25.3±11.1 years were recorded before the pandemic and were statistically significant (F=64.260, p=0.004). More malignant cases of 48(57.1%) with a mean age of 47.5±11.7 years were recorded during the pandemic. The diagnosis of malignant tumours was statistically significant between both periods (F=183.550, p=0.001). The ANN model predicted a 25% reduction in breast tumour diagnosis during the pandemic. There was a 100% impact of the pandemic on tumour type, the nature of specimen, and mean age of subjects. The COVID-19 pandemic disrupted the assessment of healthcare services as a smaller number of women were diagnosed with breast tumours during the period. This may have caused delays and late presentation leading to the diagnosis of more malignant tumours. There is a need to put adequate measures to encourage the assessment of diagnostic services during pandemics as delays may lead to an increase in morbidity and mortality